1991
DOI: 10.1148/radiology.178.2.1987596
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying in infants and children: limited utility of 1-hour measurement.

Abstract: Gastric emptying measurements were performed in infants and children at 1 and 2 hours after a liquid feeding. The 1-hour measurements were predictive of only 58% of the variability in the 2-hour measurements, indicating that the 1-hour measurement was not a good predictor of the 2-hour measurement. Gastric emptying measurements in children should be continued until 2 hours after feeding unless rapid emptying is observed during the 1st hour of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Three patients delayed at 1 hr had a normal emptying rate at 2 hr. The ability of the 1-hr emptying to predict 2-hr emptying has previously been shown to be suspect in pediatric liquid emptying studies (26). In adults, 4-hr emptying studies have been found to be superior to 2-hr studies with a standardized meal utilizing egg substitute, superior to a liquid meal (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Three patients delayed at 1 hr had a normal emptying rate at 2 hr. The ability of the 1-hr emptying to predict 2-hr emptying has previously been shown to be suspect in pediatric liquid emptying studies (26). In adults, 4-hr emptying studies have been found to be superior to 2-hr studies with a standardized meal utilizing egg substitute, superior to a liquid meal (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using scintigraphy to determine the rate of gastric emptying in healthy term infants have yielded inconsistent results. While some studies have reported faster gastric emptying in older infants, a large recent study found that infants less than 3 months of age have faster gastric emptying than older infants and children [17,18,19]. As expected, gastric emptying is twice as fast in infants fed breast milk compared to formula [20].…”
Section: Discussionmentioning
confidence: 68%
“…Measurements of gastric emptying in children should be continued until 2 hours after feeding [9]. In addition, whether a liquid or solid meal is used for GES and the age of the patient can play significant roles in the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%